Students’ perception of learning in an internship in community pharmacies (Research, Society and Development, 2022)
Objective: The aim of this study was to evaluate the perception of pharmacy undergraduate students about the learning developed in an internship in community pharmacies designed based on experiential learning theory. Methods: This was an observational study. Data were collected through a questionnaire with pharmacy internship students (n=129), including items about the student’s perception of the achievement of learning objectives and methods. Quantitative and qualitative analysis of the data were performed. Results: Most undergraduates agreed that the internship increased their understanding of the current profile of pharmacists and their responsibilities in the community pharmacy, prepared them for patient care and fostered critical assessment and ability to propose improvements. Students supervised by preceptors who performed clinical services were more likely to agree that the internship achieved the learning objective of preparing them for care. Conclusion: The majority of students agreed that the learning outcomes were achieved. The findings can contribute to improvements in internship programs, such as qualifying the practice sites.